A Freeze-drying System Coupled by DSC and Microscopy and Its Experimental Study (Zhileng xuebao)
A vacuum freeze-drying device was built and combined with differential scanning calorimetry(DSC) and microscopy,namely hereafter the freeze-drying system coupled by DSC and microscopy.By using the freeze-drying system coupled by DSC and microscopy,the freeze-drying experiments were carried out on a cryoprotectant aqueous 10%(g/g) trehalose solution supplemented with 1%(g/g) polyvinyl alcohol in order to investigate the effects of freezing condition,especially freezing rate and filling volume of the solution...